Enhancing Students’ Learning Discipline Through Reinforcement - Fajar Rifki Fauzan; Farida Agus Setiawati (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2022)
This two-cycle classroom action research aimed to improve SMPN 1 Salawu students’ learning discipline through reinforcement techniques.   Each cycle consisted of two meetings with three subjects, totaling six meetings in each cycle. Participants were six 7th-grade students recruited using a purposive sampling technique. The data were collected through observation and analyzed using descriptive analysis. The result showed an increase in learning discipline after researchers and teachers improved the reinforcement technique in the second cycle. In Cycle I, students’ dressing discipline mean score was 64%, implying a 50.5% increase from the baseline score of 12.5%. The mean score of discipline in submitting assignments was 41.7%, increasing from the baseline score of 10%.   At the end of cycle I, although the action research had met the process criteria (i.e., obtaining at least a 10% increase), it had not met the outcome criteria (i.e., mean score of 65%). In Cycle II, participants’ dressing discipline score was 94%, suggesting a 30% increase from Cycle I. Meanwhile, the discipline in submitting assignment was 81%, suggesting a 39.3% increase from cycle I.   The result of Cycle II met the process and outcome criteria, meaning that Students’ learning discipline in SMPN 1 Salawu was improved through the reinforcement technique. This result could be used as a reference for school counselors in using reinforcement techniques to improve students’ discipline.